Exploring the Profound Impact of Artificial Intelligence Applications (Quillbot, Grammarly and ChatGPT) on English Academic Writing: A Systematic Review - Bareq Raad Raheem; Farheen Anjum; Zanyar Nathir Ghafar (International Journal of Integrative Research, 2023)
The term "artificial intelligence" (AI) refers to a technology that has been established in contemporary culture and is enduring a revolutionary influence on a broad variety of sectors, including academic writing. The word "artificial intelligence" (AI) was coined by computer scientist John McCarthy in 1956. The purpose of this research is to do a comprehensive analysis of prior research that has been done on the important influence those AI systems, in particular QuillBot, Grammarly, and ChatGPT, have had on academic writing in English. This analysis will be carried out by looking at previous research in great detail. The functions and features of each AI tool, as well as user experiences and levels of satisfaction, the effect on writing productivity, the influence on writing quality, and possible ethical concerns, are investigated in this article. Also included are the possibilities for these issues to arise. In addition to this, the functions and characteristics of the user interfaces that correspond to each tool are also mentioned